ANALISIS PEMBIAYAAN PENDIDIKAN DI SMPIT DAARUL ISTIQLAL TAHUN 2023 - Fahma Balqis, Aulia; Daryanto, Eka; Restu, Restu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to analyze the sources of education funds, the use of operational costs and investment costs, and the impact of operational and investment costs on education. This research was conducted at SMP IT Daarul Istiqlal in March. The research method used is a qualitative method and the data analysis technique is descriptive, data collection techniques with direct observation, interviews, and checklists. The results showed that education financing consists of two types of financing, namely operational costs, and investment costs.